Adaptive dynamics : the theoretical analysis of behavior - Staddon, J. E. R. (MIT Press, 2001)
In this book J.E.R. Staddon proposes an explanation of behavior that lies between cognitive psychology, which seeks to explain it in terms of mentalistic constructs, and cognitive neuroscience, which tries to explain it in terms of the brain. Staddon suggests a new way to understand the laws and causes of learning, based on the invention, comparison, testing, and modification or rejection of parsimonious real-time models for behavior. The models are neither physiological nor cognitive: they are behavioristic. Staddon shows how simple dynamic models can explain a surprising variety of animal and human behavior, ranging from simple orientation, reflexes, and habituation through feeding regulation, operant conditioning, spatial navigation, stimulus generalization, and interval timing.